2007
DOI: 10.1094/mpmi-20-2-0138
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a nodH Ortholog from the Alfalfa-Nodulating Or191-Like Rhizobia

Abstract: Nodulation of Medicago sativa (alfalfa) is known to be restricted to Sinorhizobium meliloti and a few other rhizobia that include the poorly characterized isolates related to Rhizobium sp. strain Or191. Distinctive features of the symbiosis between alfalfa and S. meliloti are the marked specificity from the plant to the bacteria and the strict requirement for the presence of sulfated lipochitooligosaccharides (Nod factors [NFs]) at its reducing end. Here, we present evidence of the presence of a functional nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
9
0
9
Order By: Relevance
“…LPU83 strain is acid tolerant and has an extended nodulation host range (Del Papa et al, 1999). The genetic structure of this strain is unique in that it has a chromosome related to the bean-, pea-, and clover-nodulating rhizobia, while the pSym genes participating in nodulation and nitrogen fixation are more similar to those present in Medicago symbionts (Laguerre et al, 2001;Del Papa et al, 2007;Torres Tejerizo et al, 2011a). Previously, we described the conjugative properties of plasmids from Rhizobium sp.…”
Section: Introductionmentioning
confidence: 99%
“…LPU83 strain is acid tolerant and has an extended nodulation host range (Del Papa et al, 1999). The genetic structure of this strain is unique in that it has a chromosome related to the bean-, pea-, and clover-nodulating rhizobia, while the pSym genes participating in nodulation and nitrogen fixation are more similar to those present in Medicago symbionts (Laguerre et al, 2001;Del Papa et al, 2007;Torres Tejerizo et al, 2011a). Previously, we described the conjugative properties of plasmids from Rhizobium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Researches have indicated that at least two sets of sulfate activation systems exist in Rhizobium: one activates sulfate for the synthesis of cysteine, and APS directly generates sulfite catalyzed by APS reductase (cysH) (Sekowska et al 2000); the other is that sulfate is catalyzed to generate PAPS by ATP sulfurylase and APS kinase complex encoded by nodPQ gene, then PAPS is used to modify Nod factors and extracellular polysaccharides via sulfotransferase encoded by nodH gene (Ehrhardt et al 1995;Del Papa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lamentablemente, la estructura de los NFs de dicho mutante nodH no fue determinada, dejando abierto el interrogante de si podía existir otra enzima que produzca la sulfatación de los NFs o si esta cepa es capaz de nodular alfalfa sin poseer factores de nodulación sulfatados (Del Papa, et al, 2007).…”
Section: I6c Propiedades Simbióticas De Los Rizobios Tipo Oregonunclassified
“…Estos resultados, sin embargo, no fueron decisivos (Eardly, et al, 1992). Con la llegada de métodos filogenéticos más poderosos, Laguerre et al (2001) Papa et al (2007) estudiaron el gen nodH y encontraron relaciones filogenéticas similares a las descriptas previamente con respecto a los genes simbióticos (Laguerre, et al, 2001).…”
Section: I6dunclassified
See 1 more Smart Citation